Positioning the Writing Centre - David A. Burke (Nordic Journal of Information Literacy in Higher Education, 2020)
Implicit in the discussion about the “open” future of the library are questions about the library’s identity in an increasingly digital context and anticipations of change (Anderson et al., 2017). But the “open” future of the library does not need to be a passive future. Much like the traditional library, whose books and reading rooms were positioned between students and faculties, the future library can still occupy a similar liminal space, even as digital access supplants books and librarians do less shushing.